Pengaruh Manajemen Modal Kerja Terhadap Kinerja Keuangan Pada Perusahaan Sektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia - Novika Gea; Ihsan Effendi; Ahmad Prayudi (Universitas Medan Area, 2021)
The study aims to determine the effect of working capital management on financial performance in transportation sector companies listed on the Indonesian Stock Exchange. This research was conducted in North Sumatra Province. The data used in this study comes from annual reports of Transportation Sector companies listed on the Indonesian Stock Exchange in 2013-2018. The population of this research are 46 companies and the sample are 4 companies. Data analysis technique used is descriptive analysis and multiple regression analysis panel data Eviews. The panel data model selection used is the Fixed Effect Model (FEM). The results of this study indicate that Working Capital Turnover (WTO) has a significant positive effect on Return On Assets. (ROA), Cash Turnover (CTO) does not have a significant negative effect on Return On Assets (ROA), and Inventory Turnover (ITO) does not have a significant positive effect on Return On Assets (ROA).